Perennial vegetable gardening [videorecording (DVD)] : with Eric Toensmeier (Chelsea Green Publishing, 2012)
Presents a culmination of workshops recorded in Mexico, Florida, and Massachusetts that introduce gardeners to more than 100 species of little-known plants that can be grown for use in perennial vegetable gardens.